2020
DOI: 10.1002/hep.31142
|View full text |Cite
|
Sign up to set email alerts
|

Serial Transient Elastography Examinations to Monitor Patients With Type 2 Diabetes: A Prospective Cohort Study

Abstract: BaCKgRoUND aND aIMS: Type 2 diabetes is an important risk factor for nonalcoholic fatty liver disease (NAFLD) and advanced fibrosis. Current international guidelines recommend the use of noninvasive tests as initial assessments for NAFLD, but the role of noninvasive tests as monitoring tools has not been established. We aimed to study the role of transient elastography as a monitoring tool in patients with type 2 diabetes. appRoaCH aND ReSUltS: We recruited patients with type 2 diabetes without viral hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 30 publications
2
58
1
Order By: Relevance
“…Admittedly, a single TE result in our cross-sectional study may not be a true reflection of patient’s fibrosis status as it can be confounded by several factors such as obesity, alcohol/food consumption, or operator-dependence. Indeed, a prospective study by Lee et al investigating serial TE examinations in T2DM patients demonstrated that more than half of the patients had LSM reduction in 3 years [ 31 ]. Nevertheless, TE has been endorsed as an alternative to liver biopsy by international guidelines in guiding clinical management of chronic liver disease, including NAFLD [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, a single TE result in our cross-sectional study may not be a true reflection of patient’s fibrosis status as it can be confounded by several factors such as obesity, alcohol/food consumption, or operator-dependence. Indeed, a prospective study by Lee et al investigating serial TE examinations in T2DM patients demonstrated that more than half of the patients had LSM reduction in 3 years [ 31 ]. Nevertheless, TE has been endorsed as an alternative to liver biopsy by international guidelines in guiding clinical management of chronic liver disease, including NAFLD [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 14 out of 34 patients, paired liver biopsies were available and the changes in LSM were shown to have correlation with the change in histological fibrosis stage. In a large scale study of 611 diabetic patients conducted by Lee et al, monitoring by TE could identify fibrosis progression (from LSM < 10 kPa to LSM ≥ 10 kPa) and steatosis progression (from CAP < 248 dB/m to CAP ≥ 248 dB/m) in 4.3% and 52.0% of patients, respectively, over 3 years 23 . As for the longitudinal monitoring of response to treatment for NAFLD, TE had been adopted as a monitoring tool in a few prospective studies 24 , 25 .…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, our study was the first study to evaluate the long-term treatment responses of NAFLD to bariatric surgery using TE as a monitoring tool. In the literature, TE had been tested on the roles of monitoring disease progression and response to treatment of NAFLD [21][22][23][24][25] . Suzuki et al reported the changes of LSM over 4 years in 36 patients without paired liver biopsies for monitoring disease progression of NAFLD 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The limitation is that occasionally measurements cannot be obtained in obese patients[ 49 , 77 ], reliable LSM measurements are obtained in about 80% to 90% of NASH/NAFLD patients[ 78 , 79 ]. It is noteworthy that at least three hours of fasting are necessary before evaluation with TE since a significant increase in LSM has been observed in patients with less than two hours of fasting[ 80 ]. In addition to this, there are quality standards that should be met to consider the result as adequate: At least 10 valid measurements (60% of success) and an IQR < 30%[ 81 ].…”
Section: Evaluation Of Liver Fibrosis In Nafldmentioning
confidence: 99%
“…Around 20% had advanced liver fibrosis at baseline, but only 4% developed advanced fibrosis in 3 years. Baseline BMI, ALT, and ∆ALT independently predicted LSM increase[ 80 ]. Based on this data, we could advise performing TE every three years only in patients with risk factors such as T2DM, elevated BMI, and ALT above the UNL, otherwise, TE could be performed every 5 years.…”
Section: Evaluation Of Liver Fibrosis In Nafldmentioning
confidence: 99%